Russian Soft Power in the Baltics: In the Frameworks of Neoliberalism - Isaac Park (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
Soft power, an international relations concept coined by Joseph Nye, has been used by the Russian Federation to change the political behavior of the Baltic States: Estonia, Latvia, and Lithuania. To accomplish this goal, Russia uses public diplomacy, which is used to attract the public and influence another state’s policies. Russia’s soft power strategy seeks to mobilize a single population rather than the general public. The Compatriot policy is a crucial component of Russia’s soft power policy. It seeks to create a Russia-oriented supranational identity within the ethnic Russian population of the Baltic States. Russia seeks to mobilize its audience to change the political and social orientation of the Baltic States and to foster cooperation that is favorable towards Russia’s foreign policy objectives.